Genetic similarities among four species of the Plectranthus (L’Hér.) genus - DOI: 10.4025/actascibiolsci.v32i1.880 - Juliana Magalhães Bandeira; Valmor João Bianchi; Sílvia Rubin; José Antonio Peters; Eugenia Jacira Bolacel Braga (Acta Scientiarum. Biological Sciences, 2009)
The Plectranthus genus comprises several species generally referred to as boldo, which are highly used in popular medicine due to their anti-dyspeptic, analgesic and digestion-stimulating properties. The amount of natural active principles can vary greatly in the related genotypes, which may lead to the inappropriate use of these plants. This work aimed to analyze the interspecific diversity among four species of the Plectranthus genus (P. grandis, P. barbatus, P. neochilus and P. amboinicus) and the intraspecific diversity of P. barbatus collected from different places in southern Brazil, by means of the RAPD technique. A higher genetic similarity was observed between the P. neochilus and P. amboinicus species (80%), followed by P. grandis and P. barbatus (77%). P. barbatus genotypes from Passo Fundo and Porto Alegre showed a genetic similarity which was close to 100%, while the genetic similarity for P. barbatus genotypes from other locations was higher than 96%. Although a low variability among genotypes of this species was found in this study, RAPD markers allowed a clear differentiation among the analyzed genotypes, showing a 53% mean genetic similarity, with a high correlation value (r = 0.99), which proves a high agreement between the genetic similarity and clustering data.